Unform in bandwith of the conditional distribution function with functional explanatory variable: The case of spatial data with the k Nearest Neighbour method - Bouabsa, Wahiba (Warunkowa funkcja rozkładu z funkcjonalną zmienną wyjaśniającą: przypadek danych przestrzennych i metody k-najbliższego sąsiada, 2022)
In this paper the author introduced a new conditional distribution function estimator, in short (cdf), when the co-variables are functional in nature. This estimator is a mix of both procedures the k Nearest Neighbour method and the spatial functional estimation.
Econometrics = Ekonometria, 2022, Vol. 26, No. 2, s. 30-46
Keywords: functional data analysis; non-parametric functional; spatial data analysis; k nearest neighbours method; funkcjonalna analiza danych; nieparametryczna funkcjonalna; przestrzenna analiza danych; metoda k najbliższych sąsiadów